Towards analysis of mental stress using thermal infrared tomography - Kopaczka, Marcin; Jantos, Thomas; Merhof, Dorit (Informatik aktuell, 2018)
A number of publications has focused on detecting and measuring mental stress using infrared tomography as it is a noninvasive and convenient monitoring method. Several potential facial regions of interest such as forehead, nose and the upper lip in which stress may potentially be detectable have been identified in previous contributions. However, these publications are not comparable since they all rely on different approaches regarding both experiment design (stressor, ground truth/reference measurements) as well as evaluation methodology such as either average temperature monitoring or advanced image processing methods. We therefore focus on two aspects: Designing an experiment that allows a reliable induction of mental stress and measuring temperature changes in all aforementioned regions as well as on introducing and evaluating a GLCM-based method for quantitative analysis of the recorded image data. We show that signals extracted from the upper lip region correspond well with high stress levels, while no correspondence can be shown for the other regions. The suggested GLCM-based method is shown to be more specific towards stress response than established measurements based on average region temperature.
CRIS-Team Scopus Importer:2023-03-23